Investigating the Relationship between Anxiety Physical and Subjective Symptoms amongst Students without and Exposed to Internet Addiction - Mojgan Agah Heris; Nazila Khatib Zanjani; Emelia Mirzamohammad Alaeini (Interdisciplinary Journal of Virtual Learning in Medical Sciences, 2017)
Background Self-control on Internet usage would be lost in an individual due to exposure to Internet addiction and the individual would experience negative outputs in life. The purpose of the present study is to investigate the relationship between anxiety, physical, and mental symptoms amongst students exposed to and without Internet addiction. Methods A cross-sectional descriptive study, utilizing self-report questionnaires, was conducted 2016. The statistical community consisted of 17,000 students. The sample consists of 304 students who were selected by applying the cluster sampling method. In this research, two standard instruments Young’s Internet addiction test and Beck’s anxiety questionnaire were used, where the reliability of them were accepted by 10 specialists and the validity of them were calculated by Cronbach Alpha as 0.71 and 0.92. At first, the addiction test was done in order to identify the students exposed to and without Internet addiction. After getting the scores and identifying 2 groups, an anxiety questionnaire was completed by samples. Data analysis was done by use of an independent t-test and ANOVA by SPSSv.22. Results The results showed that high total grades of anxiety and its subscales (panic, autonomic, neurophysiological, and mental) amongst students who exposed Internet addiction in comparison to other groups (P = 0.001). Furthermore, master students showed high scores in Internet addiction compared to bachelor students (P = 0.003). While there is no significant association between general anxiety, gender, and Internet addition (P > 0.001), age also does not show a meaningful relationship with Internet addiction and anxiety (P > 0.001). Conclusions The findings showed that there is a significant difference between students exposed to Internet addiction with students without Internet addiction. In reality, the students who exposed Internet addiction reported high grades of anxiety and its subscales (panic, autonomic, neurophysiological and mental). In general, Internet addiction students experienced high level of anxiety and its symptoms.